Agenda ekonomi Indonesia - Prasetiantono, A. Tony (Jakarta : Gramedia Pustaka Utama & Sekolah Tinggi Ilmu Ekonomi'Yogyakarta', 1995)
Economic conditions of Indonesia ; collected articles
Includes index
Keywords: Indonesia -- Economic conditions -- 1945-; Indonesia -- Economic policy